2009
DOI: 10.1126/science.1175552
|View full text |Cite
|
Sign up to set email alerts
|

Fluxonium: Single Cooper-Pair Circuit Free of Charge Offsets

Abstract: The promise of single Cooper pair quantum circuits based on tunnel junctions for metrology and quantum information applications is severely limited by the influence of "offset" charges -random, slowly drifting microscopic charges inherent to many solid-state systems. By shunting a small junction with the Josephson kinetic inductance of a series array of large capacitance tunnel junctions, thereby ensuring that all superconducting islands are connected to the circuit by at least one large junction, we have real… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
768
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 641 publications
(794 citation statements)
references
References 21 publications
8
768
0
3
Order By: Relevance
“…Planar transmon variants such as the Xmon [4] have shorter coherence times, but have made possible demonstrations of the building blocks of quantum error correction codes [5][6][7][8]. In contrast to the transmon architecture, in which a Josephson junction is shunted capacitively, in a fluxonium qubit the shunt is via an inductance [9,10]. To realize in practice a sufficiently large inductance, arrays with many Josephson junctions are used.…”
Section: Introductionmentioning
confidence: 99%
“…Planar transmon variants such as the Xmon [4] have shorter coherence times, but have made possible demonstrations of the building blocks of quantum error correction codes [5][6][7][8]. In contrast to the transmon architecture, in which a Josephson junction is shunted capacitively, in a fluxonium qubit the shunt is via an inductance [9,10]. To realize in practice a sufficiently large inductance, arrays with many Josephson junctions are used.…”
Section: Introductionmentioning
confidence: 99%
“…Lambda configuration for the emitter can be obtained, taking advantage of the two possible biexcitonic transitions in quantum dots [16] or the different spin states in the optical transitions in a single N-V center [17], for instance. Superconducting qubits in circuit QED offer another natural playground for the exploration of 1D atoms properties [18,19]. As a matter of fact, EIT [20], single photon routing [21], and ultimate amplification [22] have been demonstrated, building on the three-level structure of transmons or superconducting loops efficiently coupled to microwave sources of two different frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…These properties are utilized for various applications such as the development of the Fluxonion for quantum information precessing 5 , development of voltage standards in metrology 6 and for widely tunable parametric amplifiers 7 . Furthermore it is suggested that very long one-dimensional Josephson junction chains formed in a transmission line geometry can be employed for creating an analog of the event horizon and Hawking radiation 8,9 .…”
Section: Introductionmentioning
confidence: 99%